Still Alice a novel - Genova, Lisa (Pocket Books, 2009)
Alice Howland, happily married with three grown children and a house on the Cape, is a celebrated Harvard professor at the height of her career when she notices a forgetfulness creeping into her life. As confusion starts to cloud her thinking and her memory begins to fail her, she receives a devastating diagnosis: early onset Alzheimer's disease.